2020
DOI: 10.1128/msphere.00793-20
|View full text |Cite
|
Sign up to set email alerts
|

The H-NS Regulator Plays a Role in the Stress Induced by Carbapenemase Expression in Acinetobacter baumannii

Abstract: Disruption of the histone-like nucleoid structuring protein (H-NS) was shown to affect the ability of Gram-negative bacteria to regulate genes associated with virulence, persistence, stress response, quorum sensing, biosynthesis pathways, and cell adhesion. Here, we used the expression of metallo-β-lactamases (MBLs), known to elicit envelope stress by the accumulation of toxic precursors in the periplasm, to interrogate the role of H-NS in Acinetobacter baumannii, together with other stressors. Using a multidr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…A previous analysis using metallo-β-lactamases (MBLs) and DNA-damaging agents as stressors 9 , showed that the AB5075 Δhns strain showed diminished ability to overcome stress 9 . Moreover, imipenem MICs of strains expressing the different MBLs, showed a detrimental impact on the antibiotic resistance phenotype in the Δ hns background 9 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous analysis using metallo-β-lactamases (MBLs) and DNA-damaging agents as stressors 9 , showed that the AB5075 Δhns strain showed diminished ability to overcome stress 9 . Moreover, imipenem MICs of strains expressing the different MBLs, showed a detrimental impact on the antibiotic resistance phenotype in the Δ hns background 9 .…”
Section: Resultsmentioning
confidence: 99%
“…A previous analysis using metallo-β-lactamases (MBLs) and DNA-damaging agents as stressors 9 , showed that the AB5075 Δhns strain showed diminished ability to overcome stress 9 . Moreover, imipenem MICs of strains expressing the different MBLs, showed a detrimental impact on the antibiotic resistance phenotype in the Δ hns background 9 . In addition, the increased susceptibility to imipenem observed in both mutant strains can be explained in part by the significant increase in expression of carO (Supplementary Table S4 , and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous analysis using metallo-β-lactamases and DNA-damaging agents as stressors 9 , showed that the AB5075 Δhns strain showed diminished ability to overcome stress 9 . Moreover, imipenem MICs of strains expressing the different MBLs, showed a detrimental impact on the antibiotic resistance phenotype in the Δhns background 9 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the growth inhibitory activity of subinhibitory concentrations (1/2 and 1/4 MICs) of cinnamic and gallic acids was determined against these isolates. All determinations were performed as triplicates using untreated growth controls ( Huang et al, 2020 ; Li et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%